2018
DOI: 10.3390/en11040914
|View full text |Cite
|
Sign up to set email alerts
|

Power Transformer Operating State Prediction Method Based on an LSTM Network

Abstract: Abstract:The state of transformer equipment is usually manifested through a variety of information. The characteristic information will change with different types of equipment defects/faults, location, severity, and other factors. For transformer operating state prediction and fault warning, the key influencing factors of the transformer panorama information are analyzed. The degree of relative deterioration is used to characterize the deterioration of the transformer state. The membership relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Також наявні роботи [11][12][13][14][15], в яких приведені методи та підходи, використання яких дозволяє здійснювати ідентифікацію та прогнозування технічного стану трансформатора.…”
Section: електричні машини і апаратиunclassified
“…Також наявні роботи [11][12][13][14][15], в яких приведені методи та підходи, використання яких дозволяє здійснювати ідентифікацію та прогнозування технічного стану трансформатора.…”
Section: електричні машини і апаратиunclassified
“…Significant work has been done by researchers to establish machine learning methods for transformer fault prediction and classification (Ghoneim 2018, Song et al 2018, Zheng et al 2018, Lin et al 2018, Liu et al 2019, Jiang et al 2019, Elânio Bezerra et al 2020, Zeng et al 2020. Most of the proposed artificial intelligent methods are based on single gas ratio interpretation methods (IEC 60599 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the RNN structure effectively predicted the running status of the hard disc. The literatures [15, 16] used a single LSTM to predict short‐term wind power and transformer operating state predictions. It achieved significant improvements in prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%